Exploring Local Culture as a Medium for Mathematics Learning in Elementary and Secondary Schools - Syarifuddin, Syarifuddin; Majid, Abdul; Danial; Awal Nur, Muhammad; Rahman, Hardianto (JTMT: Journal Tadris Matematika, 2025)
This study aims to explore and analyze several mathematical concepts contained in traditional games and traditional foods of the Bugis tribe in Bone Regency. This research is an exploratory-descriptive study with an ethnographic approach. The instrument used in this study is a human instrument, where the researcher is directly related to the research and acts as a data collector. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis techniques use an interactive model, namely data reduction, data presentation, and conclusion drawing. The results of the study show that traditional games such as mabbelle, mangngasing, mabendi bendi, mappadekko, and Mappasajang, and traditional foods such as doko doko cangkuli, barongko, and Putri sallang contain mathematical concepts consisting of flat and solid shapes such as squares, rectangles, kites, circles, pyramids, primes, and cubes. These mathematical concepts have relevance to mathematical concepts at elementary and secondary school levels in geometry material. Therefore, traditional games and traditional foods are used as a medium for learning mathematics in schools, especially elementary and secondary schools, so that learning is more innovative and meaningful and as a source of evaluation in learning mathematics related to local culture in the area.